CRIME SCENE MANAGEMENT OF LOW INTENSITY EXPLOSION NEAR AIR INDIA COLONY (Journal of Forensic Medicine & Toxicology, 2017)
On 04 -11- 2011 around 6.45 pm, the Vakola police got a call about an explosion near the Air India Colony on Kalina-Kurla road. At 7:00 pm Forensic science laboratory got call to visit at place of crime. Forensic team visited the place at 7:15 pm. It was found that the explosion took place in a wheelchair (for handicap person) at isolated area near Air India colony Santa Cruz (E), one handicapped person was injured due to explosion and crush injury was observed. From the place of crime one broken toy remote like electronic device, damaged and broken metallic container with electrical wire and circuit, metal pieces and polythene pieces were collected. Traces of gun powder like material was found in damaged metallic container. Chemical analysis revealed that remote control was used to detonate the low explosive mixture potassium nitrate, sulfur, aluminum powder i.e. gun powder.
Keywords: Air India colony blast; Gun powder bomb; IED; Helicopter bomb; Explosion by remote